Management of Locally Advanced Renal Cell Carcinoma with Invasion of the Duodenum. (3rd April 2013) - Schlussel, Andrew T.; Fowler, Aaron B.; Chinn, Herbert K.; Wong, Linda L.
Abstract : Renal cell carcinoma (RCC) is rare but aggressive, with greater than 20% of patients presenting with stage III or IV, disease. Surgical resection of the primary tumor regardless of stage is the treatment of choice, and en bloc resection of involved organs provides the only potential chance for cure. This case report describes a patient with metastatic right-sided RCC with invasion of the inferior vena cava and duodenum managed by en block resection and pancreaticoduodenectomy. This report will review the workup and treatment of locally advanced RCC, as well as the role of cytoreductive nephrectomy in the setting of metastatic disease.